2015
DOI: 10.1182/blood.v126.23.222.222
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of Intermediate-Dose Cytarabine Plus Mitoxantrone (IMA) Versus Standard-Dose Cytarabine Plus Daunorubicin (DA) for Induction Therapy in AML Patients >60 Years. Results from the SAL 60+ Trial

Abstract: Background: Most patients (pts) diagnosed with Acute Myeloid Leukemia (AML) are older than 60 years. Although intensive induction chemotherapy in medically fit pts is still the standard practice and a prerequisite for long-term survival, elderly pts have a higher risk of treatment related morbidity and lower remission rates than younger AML pts. An optimized induction treatment would combine high complete remission (CR) rates with tolerable toxicity. The combination of intermediate-dose cytarabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The NCRI AML17 trial did differ from that of Lowenberg and colleagues in that it used a double induction strategy, so results between the two trials are difficult to compare. Similarly, a number of trials in elderly AML patients have investigated the utility of dose-dense induction regimens with escalated cytarabine doses such as IMA and TAD-HAM/HAM-HAM (see Table 2 for regimen description) but have shown no OS benefit with these regimens [16,17]. Based on these results, an induction regimen of infusional cytarabine for 7 days with daunorubicin 60mg/m 2 daily on days 1-3, commonly referred to as '7 + 3', has become standard in the USA for fit, newly diagnosed AML patients age 60 and above.…”
Section: Induction Approachesmentioning
confidence: 99%
“…The NCRI AML17 trial did differ from that of Lowenberg and colleagues in that it used a double induction strategy, so results between the two trials are difficult to compare. Similarly, a number of trials in elderly AML patients have investigated the utility of dose-dense induction regimens with escalated cytarabine doses such as IMA and TAD-HAM/HAM-HAM (see Table 2 for regimen description) but have shown no OS benefit with these regimens [16,17]. Based on these results, an induction regimen of infusional cytarabine for 7 days with daunorubicin 60mg/m 2 daily on days 1-3, commonly referred to as '7 + 3', has become standard in the USA for fit, newly diagnosed AML patients age 60 and above.…”
Section: Induction Approachesmentioning
confidence: 99%
“…Since the European Organization for Research and Treatment of Cancer Leukemia Group trial demonstrated an increased survival rate on intensive induction chemotherapy compared to best supportive care in elderly AML patients, there have been studies to determine the standard regimen. Most studies enrolled patients over the age of 60 and attempted a treatment combination of cytarabine and anthracycline [ 6 , 7 , 8 ]. These studies showed that intensive chemotherapy could be an effective treatment option for selected elderly AML patients.…”
Section: Introductionmentioning
confidence: 99%